Using a private cloud based on the ProxmoxVE distribution in the educational process - D. Ye. Vankevych; H. H. Zlobin (Academy of Cognitive and Natural Sciences, 2013)
Training specialists in computer science requires the formation of students, in addition to theoretical knowledge, modern practical knowledge and skills. However, the performance of some practical tasks in general use laboratories can lead to temporary incapacitation of both individual workstations and the laboratory as a whole. The use of virtualization systems in the educational process allows full access of students to operating systems without the risk of incapacitation of PCs. Deployment of private clouds based on ProxmoxVE distribution ensures that computer science students learn cloud technologies on their own equipment of a higher education institution, which reduces hardware costs and increases the reliability of support for the learning process.